FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA PEMERINTAH DAERAH KABUPATEN/KOTA DI INDONESIA (Tahun Anggaran 2011-2012) - Devi Intan Saputri (AKT 16 UMY 046, 2016)
This research is to analyze the factors that influence the work performance of district/city government in Indonesia during the period of 2011-2012. This research used secondary data from data gathered by data gathering council and was published to society. The method used was double linier regression model. Based on the analysis that has been done, the result shows that the size of the government, the size of the area, the size of the legislative power, and audit finding have significant influence towards the working performance of district/city government, while the index of human development has no significant influence towards the working performance of district/city governmen